Increased Frequency of Self-Reported Obsessive-Compulsive Symptoms in Patients with Functional Movement Disorders - Nováková, Lucia; Anýž, Jiří; Forejtová, Zuzana; Rošíková, Tereza; Věchetová, Gabriela; Sojka, Petr; Růžička, Evžen; Serranová, Tereza (Movement disorders clinical practice, 2023)
BACKGROUND: Functional movement disorders (FMD) are associated with a high prevalence of psychiatric comorbidities. OBJECTIVE: To assess the frequency of obsessive-compulsive symptoms (OCS) in FMD. METHODS: A total of 167 consecutive patients with clinically definite FMD (mean age = 44.4 years, standard deviation [SD] = 12.0, 119 females) and 145 healthy controls (mean age = 43.2 years, SD = 11.8, 103 females) completed the Obsessive-Compulsive Inventory-Revised (OCI-R), which is a widely used tool for assessing OCS. The cutoff score ≥21 is indicative of clinically significant obsessive-compulsive disorder (OCD). Motor symptom severity was assessed using the Simplified FMD Rating Scale (S-FMDRS). All subjects completed questionnaires for depression, anxiety, pain, fatigue, cognitive complaints, health-related quality of life, and childhood trauma. Personality traits were assessed using the Big Five questionnaire. RESULTS: FMD patients had higher mean OCI-R score and higher proportion of individuals with OCI-R ≥ 21 42%, 95% confidence interval (CI) = (30.2, 54.6) versus 16%, 95% CI = (8.2, 28.2) in controls, P < 0.001. Patients had higher scores in three domains: checking, ordering, and obsessing (P < 0.001). FMD patients with OCI-R score ≥21 had higher depression, anxiety, cognitive complaints, and lower quality of life compared to those with score <21 (P < 0.001). No correlation between OCI-R and S-FMDRS scores was found. CONCLUSIONS: FMD patients reported higher rates of OCS compared to controls, along with higher rates of non-motor symptoms and lower quality of life. This finding may have clinical implications and raises the possibility of shared risk factors and common pathophysiological mechanisms in FMD and OCD.